Crystallography of phase transformation in the self-inclined InAs nanowires grown on GaAs111. (August 2016) - Liu, Zhilin; Zhang, Zhi; Jiang, Ripeng; Li, Xiaoqian; Zhang, Mingxing; Qiu, Dong
Abstract: During growth of InAs nanowires (NWs) on GaAs111, the self-inclined InAs NWs were reproducibly observed. At the self-inclined interface, the h.c.p. InAs phase was transformed into another f.c.c. InAs phase. In order to investigate the crystallography of phase transformation, a recently-developed model, edge-to-edge matching (E2EM), was applied in such self-inclined NWs for crystallographic investigation. The orientation relationships (ORs), between f.c.c. InAs and h.c.p. InAs, were predicted using the E2EM model, which agrees well with experimental results. The results indicate the importance of crystallographic study in design and construction of nanostructured semiconductors with improved physical properties. Graphic abstract: (a) The preferred orientation relationships (ORs) between catalyst and ZB, ZB and WZ, and WZ and substrate; (b) simulated superimposed diffraction patterns along the zone axis 10 1 ̅ ZB / / 2 1 ̅ 1 ̅ 0 WZ, showing the E2EM-predicted OR between ZB and WZ. The rotation angles between two corresponding matching plane-pairs, 1 1 ̅ 1 ZB / / 000 2 ̅ WZ and 1 ̅ 1 ̅ 1 ̅ ZB / / 01 1 ̅ 1 WZ, are 0.01° and 5.54°, respectively. All Δg s are perpendicular to the interface trace (dashed line).